3D Culture Modelling: An Emerging Approach for Translational Cancer Research in Sarcomas - Heredia-Soto, Victoria; Redondo, Andrés; Kreilinger, José J. P.; Martínez-Marín, Virginia; Berjón, Alberto; Mendiola, Marta (Current Medicinal Chemistry, 2020)
Sarcomas are tumours of mesenchymal origin, which can arise in bone or soft tissues. They are rare but frequently quite aggressive and with a poor outcome. New approaches are needed to characterise these tumours and their resistance mechanisms to current therapies, responsible for tumour recurrence and treatment failure. This review is focused on the potential of three-dimensional (3D) in vitro models, including multicellular tumour spheroids (MCTS) and organoids, and the latest data about their utility for the study on important properties for tumour development. The use of spheroids as a particularly valuable alternative for compound high throughput screening (HTS) in different areas of cancer biology is also discussed, which enables the identification of new therapeutic opportunities in commonly resistant tumours.
Keywords: in vitro models